A game of thrones—Dynamics of internal CEO succession and outcome. (24th May 2021) - Blank, Brian; Hadley, Brandy; Minnick, Kristina; Rivolta, Mia L.
Abstract: We examine the implications of chief executive officer (CEO) succession methods for firm outcomes and executive incentives. Focusing on internal CEO successions, we find that the largest U.S. firms typically rely on two types of succession methods, namely, heir apparent and horse race successions. Although heir apparent and horse race CEO candidates have similar qualifications, the consequences of these two succession methods differ significantly. We find that horse race successions induce conflict and are detrimental to firm performance but not necessarily to the newly appointed CEOs. Our findings suggest succession method influences firm performance, executive incentives and CEO labour markets.